Antidepressant-induced Remission of Gardner Diamond Syndrome - Neena Sanjiv Sawant (Indian Journal of Psychological Medicine, 2012)
We describe the clinical presentation of a 25-year-old female patient who presented in dermatology with recurrent episodes of painful ecchymotic bruising over the anterior aspect of both arms and face. On enquiry, these episodes were precipitated by emotional stress and were preceded with a history of fall from the stairs. The patient also had multiple stressors in her day-to-day life and symptoms of depression. A diagnosis of mild depressive disorder without somatic complaints and Gardner Diamond syndrome was made. The patient was started on antidepressants, which not only improved her mood symptoms but also caused a remission of her painful bruises.